Acceptance of Pak Choy Sticks as a Culinary Innovation in the Creative Economy of Ngrombo Baki Sukoharjo Tourism Village - Wahyu Tri Hastiningsih; Prasiwi Citra Resmi (CV. Syntax Corporation Indonesia, 2024)
Ngrombo Village is a tourist village in Sukoharjo. Ngrombo Tourism Village provides hydroponic education packages, focusing on cultivating pak choy vegetables. However, after the post-harvest process, residents only sell the pak choy as fresh vegetables without further processing. This reduces the potential selling value of pak choy, which could be increased. One option for processing pak choy is to make pak choy sticks. This research aims to determine the materials and methods for making pak choy sticks and the public's acceptance of hybrid pak choy sticks. This quantitative and descriptive research involved conducting a direct survey at locations producing pak choy in Ngrombo Village, Baki, Sukoharjo. The quantitative aspect refers to data analysis using statistics and numbers, while the descriptive aspect involves determining the frequency distribution of respondents' answers through a questionnaire distributed to selected respondents. The data obtained is then processed using statistical analysis to help researchers draw conclusions. The results of this research indicate that the ingredients for making pak choy sticks include pak choy, wheat flour, tapioca flour, corn flour, baking powder, chicken stock powder, garlic, salt, pepper, eggs, and margarine. The method involves mixing the ingredients, kneading, flattening, cutting, and frying. An organoleptic test conducted with 35 panelists revealed that the pak choy sticks had a distinctive aroma, a savory taste, a crunchy texture, a dominant green color, and were generally well-liked by the panelists.